Effect of Computer Simulation on Students’ Achievement In Probability Based on Their Attitude Toward Mathematics - Wilfred Mogire, Monyoro (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The study was about the effect of computer simulation on students’ achievement in Probability based on their attitude towards mathematics. Data were collected from 198 Form 3 students from four (4) public secondary schools who were purposefully chosen to participate in the study. To obtain qualitative and quantitative data, the researcher used students' questionnaires. The study used Post Hoc Tukey's (HSD) test and an ANOVA, and the results showed that the strategy's use had a greater impact on the experimental groups than the control groups. Statistical Package for Social Sciences (SPSS) software was typically used to quantitatively examine the data that was obtained. Depending on the research hypothesis, either a one-way ANOVA or a two-way ANOVA was used to test the hypothesis at a 95% level of significance. Additional tests were based on factor analysis, post hoc analysis, and t-tests. The main finding is that CBS's teaching approach is better than traditional approaches to teaching probability.